Atazanavir/Ritonavir Increased Tizoxanide Exposure from Oral Nitazoxanide through Pharmacokinetic Interaction in Healthy Volunteers - Abdulafeez Akinloye; Timothy Oyedeji; Oluwasegun Eniayewu; Babatunde Adeagbo; Oluseye Bolaji; Steve Rannard; Andrew Owen; Adeniyi Olagunju (MDPI AG, 2024)
Nitazoxanide use is limited by gastrointestinal side effects associated with increasing dose. In this drug repurposing study, we investigated the possibility of enhancing the exposure of its active metabolite, tizoxanide, through pharmacokinetic interaction with atazanavir/ritonavir. In this crossover drug-drug interaction study, 18 healthy participants received a single dose of 1000 mg of nitazoxanide alone and in combination with 300/100 mg atazanavir/ritonavir in period 1 and 2 respectively. On both days, blood samples for intensive pharmacokinetic analyses were collected at 0-12 h post-dose. To explore the utility of dried blood spots (DBS) as an alternative to plasma for tizoxanide quantification, 50 µL of blood from some participants was spotted on DBS cards and correlated with plasma concentrations. Pharmacokinetic parameters were derived by non-compartmental analysis and compared between both periods. Co-administration of nitazoxanide with atazanavir/ritonavir resulted in a significant increase in tizoxanide plasma exposure [GMR (90% CI) of AUC0-12h, Cmax and C12h being 1.872 (1.870-1.875), 2.029 (1.99-2.07) and 3.14 (2.268-4.352), respectively]. DBS concentration (%CV) was 46.3% (5.6%) lower than plasma concentrations, and there was strong correlation (R = 0.95, p < 0.001) between DBS-derived plasma concentration and plasma concentrations. Co-administration with atazanavir/ritonavir enhanced tizoxanide exposure with no report of adverse events in healthy volunteers.